INFLUENCER MARKETING, CULTURAL SENSITIVITY, AND ARTIFICIAL INTELLIGENCE AS DETERMINANTS OF GREEN AGRI-FOOD PRODUCT PURCHASE: THE MODERATING ROLE OF LEGAL NORM COMPLIANCE - Zdravković, Stefan; Spalević, Žaklina; Ignjatović, Jelena; Živković, Jelena (Economics of Agriculture, 2026)
Sustainable consumption and the transition toward greenproducts, particularly in the agri-food sector, representimportant challenges for contemporary agriculturaleconomics. This study examines the influence of influencermarketing, cultural sensitivity, and artificial intelligenceon consumers’ purchase intentions toward green products,with compliance with legal norms as a moderating factor.The research was conducted in the Republic of Serbiausing a survey-based methodology on a sample of 418respondents. The results show that all examined factorshave a statistically significant positive effect on greenproduct purchase, while compliance with legal normsstrengthens these relationships. The findings indicate thatsustainable consumption is driven by the interaction ofdigital communication, cultural alignment, technologicalsupport, and regulatory trust. It is recommended thatagricultural producers and food marketers combine digitalmarketing tools with culturally adapted communicationwhile ensuring adherence to legal standards. The studyprovides insights for policymakers supporting sustainableagri-food market development.